A Noval Method of Formulating and Evaluating Oral Floating In situ Gel of Metoprolol Succinates an Anti-Hypertensive Drug - Archana D. Kajale; A. V. Chandewar (Medical Science: Trends and Innovations Vol. 11, 2025)
Drugs that are easily absorbed from the gastrointestinal tract (GIT) and have short half-lives are eliminated quickly from the systemic circulation, so Frequent dosing of these drugs is required to achieve suitable therapeutic activity. To avoid this limitation, the development of oral sustained-controlled release formulations is an attempt to release the drug slowly into the GIT and maintain an effective drug concentration in the systemic circulation for a long time. Gastro-retentive in situ gel-forming system offers a suitable way of providing controlled drug delivery within the stomach where an environment-specific gel-forming solution, on conversion to gel, floats on the surface of the gastric fluids (due to less density than gastric contents). This study is an attempt at design development and evaluation of gastro retentive oral floating in situ gel of metoprolol succinate. In this proposed technique, a solution of low viscosity is used which on coming in contact with the gastric fluids, undergo a change in polymeric conformation viscous gel of density lower than the gastric fluids is produced. In the present research work, an oral floating In situ gel of Metoprolol Succinate was formulated using Sodium alginate, Chitosan, Gellan Gum, and Carbapol 940 in a different ratio. The optimized batch (sodium alginate 2%: Gellan Gum 1%) in the ratio 2:1 gave a release of the drug for 12 hours. In vivo study was performed by providing the formulation to rabbit and then X-rays were taken for the confirmation of formation of gel in the stomach and floating of dosage form for 12 hrs. It was found to be floating for 12 hrs. The optimized formulation was found to be stable for 6 Months in accelerated stability studies. The objective of increasing residence time in the stomach, reducing dosing frequency, safety profile etc. was achieved. Compared to conventional suspensions, these in situ gel preparations can be easily formulated in bulk, it gives site-specific drug delivery and sustained action when compared to other conventional suspensions.